Kompetensi Widyaiswara di Era Digital dan Media Sosial - Hasan Ashari; Sancoko, Bambang (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2021)
Digital transformation is the government's main concern which represented by technology and social media-based services. This concept also adapted to civil servant development and training programs which becomes the main task for Widyaiswara. This study aims to describe the widyaiswara's competencies, appropriate digital and social media, and the collaborative patterns of training institutions in the digital era. The research is descriptive, and analyze using the literature review method. The result shows us five major competencies which are important, namely: information and data literacy, communication and collaboration, digital content creation, digital security, and technical problem-solving. The user also needs to choose the right digital and social media platform since the usage of those by training institution tend to increase efficiency and, moreover, government income sources. There are several recommendations for widyaiswara from this research, such as: the need to increase digital competency, the need of ethical code in a digital era, and the need for regulation that possible government to get revenue from social media.